Implementation of Restorative Justice and Rehabilitative Justice Through the Diversion and Islah Process at Pulang Pisau Police - Riduan, Muhammad; Soeradji, Elvi (Transformatif, 2024)
This research is field research. The approach used in this problem is a juridical-empirical approach. Qualitative descriptive data analysis techniques. Empirical data collection was carried out by means of interviews with several research subjects and informants, which is a means of collecting data from sources that are correlated with existing literature such as national journals, international journals, books, regulations, and so on in order to provide comprehensive results so that they become a unified whole. intact. The implementation of diversion settlement by the Pulang Pisau Police is an action taken to overcome legal violations without involving a formal judicial process. This legal process is also related to the Islah theory in the Islamic view of resolving disputes that occur in society. The implementation of restorative justice and rehabilitative justice through diversion and Islah processes makes it possible to provide a more holistic and responsive response to the needs of children involved in criminal acts. This approach helps minimize stigmatization, promote social responsibility, and improve relations between children and the communities in which they live. It is hoped that public awareness of Islamic teachings can prevent and resolve conflicts better. Islah encourages community empowerment so that they can be an active part in solving their own problems. Resolving diversion and Islah by prioritizing public awareness of Islamic teachings is expected to be able to prevent and resolve conflicts better. Islah encourages community empowerment so that they can be an active part in solving their own problems.